Turicibacter fermentation enhances the inhibitory effects of Antrodia camphorata supplementation on tumorigenic serotonin and Wnt pathways and promotes ROS-mediated apoptosis of Caco-2 cells - Lin, Ting-Chun; Soorneedi, Anand; Guan, Yingxue; Tang, Ying; Shi, Eleanor; Moore, Matthew D.; Liu, Zhenhua (Frontiers in Pharmacology, 2023)
Diet-induced obesity has been shown to decrease the abundance of Turicibacter, a genus known to play a role in the serotonin signaling system, which is associated with colorectal tumorigenesis, making the presence of Turicibacter potentially influential in the protection of intestinal tumorigenesis. Recently, Antrodia camphorata (AC), a medicinal fungus native to Taiwan, has emerged as a promising candidate for complementary and alternative cancer therapy. Small molecules and polysaccharides derived from AC have been reported to possess health-promoting effects, including anti-cancer properties. The present study aims to determine the role of Turicibacter in colorectal tumorigenesis and to explore the anti-cancer mechanism of AC with Turicibacter fermentation. Our results show that Turicibacter fermentation and the addition of AC supplementation led to a significant increase in the production of nutrients and metabolites, including α-ketoglutaric acid and lactic acid (p < 0.05). Treatment of Turicibacter fermented AC supplementation was effective in inhibiting serotonin signaling-related genes, including Tph1, Htr1d, Htr2a, Htr2b, and Htr2c (p < 0.05), and Wnt-signaling related protein and downstream gene expressions, such as phospho-GSK-3β, active β-catenin, c-Myc, Ccnd1, and Axin2 (p < 0.05). Additionally, it triggered a significant increase in the generation of reactive oxygen species (ROS), which activated PI3K/Akt and MAPK/Erk signaling and resulted in cleaved caspase-3 expression. In comparison, the treatment of AC supplementation without Turicibacter fermentation displayed a lesser effect. In summary, our findings suggest that AC supplementation effectively suppresses the tumorigenic serotonin and Wnt-signaling pathways, and promotes ROS-mediated apoptosis in Caco-2 cells. These processes are further enhanced by Turicibacter fermentation.